Bibliometric Analysis of Religious Tolerance Research Trends: Indonesia's Role in Global Studies - Arifurrohman; Crismono, Prima Cristi (JURNAL PENELITIAN, 2025)
This study examines the trends and development of academic research on religious tolerance using bibliometric methods and data from Scopus, analyzed through VOSviewer. The findings show that scholarly attention peaked in 2017, with a subsequent decline up to 2024, reflecting shifts in academic focus from social prejudice to themes such as religious pluralism, interfaith relations, and education’s role in fostering tolerance. Indonesia plays a central role in this global discourse, particularly through the practice of Islamic moderation and the contributions of religious organizations such as Nahdlatul Ulama. Geographic analysis reveals that while the United States leads in publication volume, Indonesia ranks second, highlighting its growing influence. The study also maps thematic evolutions and keyword networks, underscoring the transition toward a deeper understanding of pluralism and inclusive social policies. Although limited by reliance on a single database and the exclusion of non-English literature, the research offers valuable insights into Indonesia’s strategic position in the global religious tolerance landscape and suggests directions for future studies on digital media, globalization, and minority experiences. These findings have significant implications for policymakers, educators, and social organizations aiming to promote peaceful coexistence in diverse societies.